Pelatihan Merajut bagi Kaum Perempuan di Perumahan Rancaekek Permai Kabupaten Bandung - Djachrab, Ida Rapida; Fatwa, Shinta Nur (Ma'soem University, 2024)
This research was motivated by the frequent gathering of some women, especially housewives in Rancaekek Permai RT 04 RW 18 Housing, Rancaekek District, Bandung Regency. Many activities are carried out ranging from activities to RT-an, botram, or just chatting. Seeing this condition, it was decided to make the gathering event a part that could increase the skills of mothers through knitting training. The method used uses PAR (Participacy Action Research). The results showed that knitting activities can provide useful skills and can even be used as additional income for the family.